HEDONIC MOTIVATION AND INFLUENCER MARKETING EFFECTS ON YSL BEAUTY PURCHASE DECISIONS: THE MEDIATING FUNCTION OF FOMO - Josephine Chandra; Rodhiah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research aims to analyze the influence of hedonic motivation and influencer marketing on purchase decisions for YSL Beauty products with Fear of Missing Out (FOMO) as a mediating variable. The study employed a quantitative approach with cross-sectional design. Data were collected through online questionnaires distributed to 218 Generation Z consumers domiciled in West Jakarta who had purchased YSL Beauty products. Analysis used Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that hedonic motivation and influencer marketing have positive and significant effects on purchase decisions both directly and indirectly through FOMO as mediation. The R² value for FOMO was 0.420 and for purchase decisions was 0.383, indicating moderate predictive capability. Influencer marketing had the strongest effect on FOMO (0.402), followed by hedonic motivation (0.356). All hypotheses were accepted with significance levels below 0.05. These findings provide theoretical contributions to consumer behavior literature in luxury cosmetics and practical implications for digital marketing strategies.